2015
DOI: 10.18632/oncotarget.6180
|View full text |Cite
|
Sign up to set email alerts
|

Anti-leukemic effects of the V-ATPase inhibitor Archazolid A

Abstract: Prognosis for patients suffering from T-ALL is still very poor and new strategies for T-ALL treatment are urgently needed. Our study shows potent anti-leukemic effects of the myxobacterial V-ATPase inhibitor Archazolid A. Archazolid A reduced growth and potently induced death of leukemic cell lines and human leukemic samples. By inhibiting lysosomal acidification, Archazolid A blocked activation of the Notch pathway, however, this was not the mechanism of V-ATPase inhibition relevant for cell death induction. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 74 publications
3
19
0
Order By: Relevance
“…Archazolid, a V-ATPase inhibitor, is highly effective against various cancer cell lines [ 158 ]. Recent research showed that Archazolid induced cell death by disturbing TFR recycling and impairing iron supply of cancer cells [ 159 , 160 ].…”
Section: Therapeutic Opportunities For Cancer Based On Altered Iromentioning
confidence: 99%
“…Archazolid, a V-ATPase inhibitor, is highly effective against various cancer cell lines [ 158 ]. Recent research showed that Archazolid induced cell death by disturbing TFR recycling and impairing iron supply of cancer cells [ 159 , 160 ].…”
Section: Therapeutic Opportunities For Cancer Based On Altered Iromentioning
confidence: 99%
“…Archazolid has been intensively investigated as anti-tumoral agent that induced apoptosis of cancer cells and reduced migration of invasive tumor cells in vitro, and decreased metastatic dissemination of breast tumors in vivo [18][19][20]. In various highly invasive tumor cell lines and leukemic cells, archazolid led to apoptosis due to activation of the hypoxia-inducible factor-1α (HIF1α) [18,21], and to anoikis induction [22]. Thus, archazolid represents a promising candidate for direct targeting of tumor cells via V-ATPase inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…ing V-ATPase activity using either pharmacological inhibitors or genetic approaches significantly reduces the invasiveness and migratory capacity of numerous cancer cell types (5,18,(21)(22)(23)(24)(25)(26)(27)(28). Specifically, plasma membrane V-ATPases appear to play a central role in cancer cell invasiveness (6).…”
mentioning
confidence: 99%